Effect of trust and perceived reciprocal benefit on students' knowledge sharing via facebook and academic performance - Moghavvemi, Sedigheh; Sharabati, Manal; Klobas, Jane Elizabeth; Ainin, Sulaiman (Academic Conferences and Publishing International, 2018)
This paper explored the effect of trust and perceived reciprocal benefit on students' knowledge sharing via Facebook and on students' academic performance and reputation. The research model was tested using 170 undergraduate students in Malaysia via structural equation modeling. The results show that trust and perceived reciprocal benefit are two strong predictors of knowledge sharing amongst students, which affects their academic performance and recognition. Students with high levels of altruism are more open to sharing knowledge without preconditions compared to those with lower levels of altruism. The findings of this research would help educational institutions use Facebook as a knowledge sharing platform and also convert their academic procedures to an e-learning environment with Facebook as its platform. Creating a virtual environment and facilitating knowledge sharing among students will encourage a more productive and constructive learning environment. Facebook groups are regarded as an online community that increase students' interaction, collaboration, and trust.